The Influence of Critical Thinking Skills and Inquiry Skills on the Biosolar Innovation Ability of Class X Students TKR Skills Competency at SMKN 1 Jiwan - Lestari, Yoni Dwi; Harimurti, Rina; Warju, Warju; Anifah, Lilik; Buditjahjanto, I Gusti Putu Asto (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
Critical thinking skills and inquiry skills are necessary for vocational school students to stimulate innovation abilities because vocational school graduates are prepared to immediately enter the world of work or create their jobs. The research goal is to analyze the influence of critical thinking skills and inquiry skills on the biosolar innovation abilities of class Light Vehicle Engineering students. It is a descriptive type of research that applies a quantitative method. It uses an ex-post de facto design. The population in this study was class X TKR Â skill competency students at SMK Negeri 1 Jiwan, totaling 129 students. With a sample size of 98 students. This study used a simple random sampling technique. The measuring instrument used is a questionnaire with multiple linear regression analysis as the data analyzing technique. The results show that there is a significant partial and simultaneous influence of the critical thinking skills and inquiry skills variables on the biosolar innovation abilities of the class The suggestion from this research is that schools are expected to be able to adopt policies that can stimulate students' biosolar innovation abilities which are influenced by critical thinking skills and inquiry skills.